THE EFFECT OF GOOD CORPORATE GOVERNANCE AND CORPORATE, SOCIAL RESPONSIBILITY ON FIRM VALUE WITH FINANCIAL PERFORMANCE AS A MODERATING VARIABLE - Muhammad Rafi Taqiyuddin; Irwan Sutirman Wahdiat (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to examine and analyze the effect of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) on Firm Value with Financial Performance as a moderating variable. The research object is financing companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024. This study uses an associative quantitative approach with secondary data obtained from annual reports and sustainability reports. The sampling technique used is purposive sampling, resulting in 12 companies as research samples. The data analysis techniques used are descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, and Moderated Regression Analysis (MRA) with the help of SPSS software. The research findings indicate that Good Corporate Governance has a positive and significant effect on Firm Value. In contrast, Corporate Social Responsibility does not have a significant effect on Firm Value. The moderating test results show that Financial Performance can moderate the effect of GCG on Firm Value in a weakening direction, but Financial Performance cannot moderate the effect of CSR on Firm Value.